The use of visible and near infrared reflectance spectroscopy to predict beef M. longissimus thoracis et lumborum quality attributes - Andrés, S. (2013)
Visible and near infrared reflectance spectroscopy was used to predict pH at 24 h (pH24) post-mortem, sarcomere length (SL), cooking loss (CL), Warner–Bratzler Shear Force (WBSF) and colour parameters (L*, a*, b*) in beef cattle samples. Samples from M. longissimus thoracis et lumborum from 30 bulls were aged at 4 C for 1, 3, 7 and 14 days and analysed for pH, SL, CL, WBSF and colour. NIRS calibrations for pH24, luminosity at 0 (L*t0) and 60 min (L*t60) showed good predictability (R2 = 0.97, 0.85 and 0.82; SECV = 0.10, 1.16, 1.36, respectively), whereas those related to the rest of the parameters were poorer